331 COVID-19 Mortality After Vascular Procedures During the Initial UK Surge: Moving Forward with Elective Vascular Work. (12th October 2021) - Liu, P; Cheema, S; Adeoye, I; Theivacumar, S; Hussain, T; Malina, M
Abstract: Aim: Following the initial COVID-19 surge in the United Kingdom, there was a national incentive for elective vascular surgery to be restricted to clean sites in order to reduce perioperative cross infection and subsequent mortality. We assessed the risk of dying from perioperatively acquired COVID-19 during the peak of the London outbreak. Method: 43 consecutive patients who had vascular (n = 48) procedures in March and April 2020 at a regional hub serving five London hospitals were analysed. The patients were screened for COVID-19 in the 30-day postoperative period and the main outcome measure was mortality from COVID-19. A comparison was then made with patients who underwent minimally invasive procedures from our integrated interventional radiology department. Median follow-up was 41 days (IQR 8- 58 days). Results: Three patients (7%) in the vascular group (median age 61 years, all diabetic, two male) died from COVID-19, all of whom tested positive postoperatively. Two others became positive but recovered. In comparison, two patients (2%) in the interventional radiology group died from COVID-19, however one was positive prior to their procedure. Conclusions: Only urgent vascular cases should be performed during a COVID-19 surge, with elective work delayed or continued at clean sites. However, with growing waiting lists for elective surgery currently, further restrictions may not be a viable long-term solution. Resumption of care at hot sites should be considered, if resources allow for it and if safety measures can be implemented. The advantages of minimally invasive surgery may inherently reduce risk as well.